Stabil'nost' pervoj podaci tennisistov na glavnych turnirach godicnogo cikla - Skorodumova, A. P.; Dolgikh, N. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The paper presents the average stability values of the first inning of the best eight tennis players at each Grand Slam tournament. The dynamics of the indicators of the average stability values of the first inning on the days of the tournament is analyzed. The average stability of the first inning in the Grand Slam tournaments is 60-67%. The best average stability in a match was 81% in only one match with one tennis player. The stability of the first inning of the leading tennis players of the world,including finalists and winners, changes in waves. Fluctuations between the best and the worst result are 5-23%. There is a deterioration in inning stability by the last game day compared to the first. The greatest stability of the first inning on average for tennis players, included in the eight strongest, recorded at the Australian Open, the least - at the US Open. The average stability values of the first inning of the eight best players in each Grand Slam tournament tend to decrease from tournament to tournament. The established tendency to reduce the stability of the first inning indicates that stability depends not so much on the coverage of the courts as on the accumulated fatigue towards the end of a long competitive period.